(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic that occurred at the end of December 2019 was a global outbreak whose symptoms were characterized by fever, dry cough, flu, and fatigue. This outbreak occurred for the first time in Wuhan China and spread to other countries including Indonesia. The call to follow the health protocol, especially in Pulorejo Village, is an ongoing effort to make the community use masks, maintain distance, wash hands with soap, and use hand sanitizers. One of the innovations that can be applied in designing an automatic hand sanitizer. With the development of this technology, residents are expected to be able to use hand sanitizer without having to come into contact with the container. This tool uses infrared sensors, cables, and batteries. In addition to helping the welfare of the community, residents can also participate in utilizing existing technology.